Study on phenol sulfonation by concentrated sulfuric acid: Kinetics and process optimization. (20th July 2019) - Ma, Xiaoke; Li, Peng; Ma, Tian-Xiang; Chu, Guang-Wen; Luo, Yong; Zou, Hai-Kui; Sun, Baochang; Chen, Jian-Feng
Highlights: The reaction kinetics of phenol sulfonation by concentrated sulfuric acid was measured in a stirred tank reactor. Effect of operating conditions on the yield and selectivity of product were optimized based on the kinetic model. The rotating packed bed (RPB) was employed to intensify the micro-mixing efficiency of phenol sulfonation process. Abstract: Sulfonation process usually exhibit high reaction rate and low yield and selectivity of product in common reactors for its insufficient micromixing. This work employed a rotating packed bed (RPB) to intensify the micromixing of the phenol sulfonation process to improve the yield and selectivity of p-hydroxybenzenesulfonic acid (p-HBSA). Experiments and kinetic study on the sulfonation of phenol by concentrated sulfuric acid were carried out in a stirred tank reactor (STR). The reaction rate constant k and activation energy E at certain temperature was tested. The values of pre-exponential factor and activation energy were obtained as follows: k 1 = 5.74 × 10 3, E 1 = 8.17 kJ/mol, k -1 = 6.95 × 10 3, E -1 = 6.18 kJ/mol, k 2 = 1.43 × 10 10, E 2 = 69.35 kJ/mol, k -2 = 0.05 × 10 3, E -2 = 14.17 kJ/mol. The effects of various operating conditions including reaction temperature ( T ), sulfuric acid/phenol molar ratio ( η ), solvent/phenol molar ratio ( ζ ), concentrated sulfuric acid feeding rate ( Q′ ), stirring speed ( P ), ageing time ( τ ), on the content of p-HBSA were investigated in an attempt to obtain the optimal operating conditions in the STR. The yield of p-HBSA is 89.85% at the optimal operating conditions. On the basis of the results in STR, further experiments were performed in a rotating packed bed (RPB) to improve the sulfonation reaction selectivity and p-HBSA yield. The effects of rotation speed ( N ), cycle time ( t ) and concentrated sulfuric acid feeding rate ( Q ) were investigated. Results show that the yield of p-HBSA can reach up to 96.52% in RPB at the optimal operating conditions of N = 2250 rpm, Q = 300 mL/min, T = 100 °C, η = 1.1, τ = 25 min, ζ = 1.25 and t = 3 min. The yield of p-HBSA obtained in the RPB is 6.67% higher than that in the STR. The research exhibits that RPB can obviously improve the yield of p-HBSA.